IMPLEMENTASI KEBIJAKAN REVITALISASI KOTA LAMA SEMARANG DALAM MENDUKUNG PARIWISATA BERKELANJUTAN - Yosua Byantika; Lusia Astrika (Journal of Politic and Government Studies, 2026)
The revitalization of the Kota Lama Semarang area is a government policy aimed at preserving historical heritage while promoting sustainable tourism development by considering economic, socio-cultural, and environmental aspects. This study aims to analyze the implementation of the revitalization policy of Kota Lama Semarang in supporting sustainable tourism. The research uses a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation, involving informants selected through purposive sampling, including government officials, area managers, local business actors, and tourists. The analysis applies the policy implementation framework developed by George C. Edwards III, which includes the dimensions of communication, resources, disposition, and bureaucratic structure. The results show that the implementation of the revitalization policy has generally been carried out well, particularly in terms of inter-agency communication and the commitment of policy implementers. The revitalization has also contributed to increasing economic activities, preserving the historical and cultural values of the area, and improving the environmental quality of the tourism destination. However, several challenges remain, such as limited community participation, suboptimal empowerment of local economic actors, and environmental management issues including waste management and visitor density. Therefore, stronger collaboration among government institutions, area managers, business actors, and the local community is needed to support sustainable tourism development in Kota Lama Semarang.